Learning Styles of Students at Pattimura University Laboratory High School - Rumahlewang, Emma; Lating, Ainun Diana; Ellis, Runawati; Mahaly, Sawal (International Journal of Education, Information Technology, and Others, 2025)
Learning styles greatly influence the quality of learning, so teachers must first know whether the students' learning styles are in accordance with their characteristics. The selection of professional teachers is very important to support the achievement of learning quality. One way to improve the quality of learning is to know the learning style. The purpose of the study was to analyze students' learning styles to improve teachers' understanding of students' learning needs. This study used a descriptive quantitative approach. The sample in this study was 30 grade XI students and the sample collection technique usedtotal sampling. The results of the study provide an overview that the highest student learning styles are first, kinesthetic learning style (30.59%), second mixed learning style (28.24%), third visual learning style (24.71%) and fourth audio learning style (16.47%). In other words, the most dominant learning style in students of SMA Laboratorium Universitas Pattimura class XI is Kinesthetic.